Monitoring the safe delivery of new invasive interventional procedures and devices: an analysis of NHS organisation policies - Leila Rooshenas; Jane M Blazeby; Sian Cousins; Lucy Wallis; Phei Yi Lim; Hollie S Richards (BMJ Open Quality)
Background The introduction and monitoring of innovative invasive procedures and devices (IP/Ds) was included in the Independent Medicines and Medical Devices Safety (IMMDS) Review led by Baroness Cumberlege. Currently, innovative IP/Ds may be undertaken with local National Health Service (NHS) organisation approval via new procedure committees (NPCs) or approval from the Health Research Authority (HRA). The National Institute for Health and Care Excellence Interventional Procedures Advisory Committee (NICE IPAC) provides guidance for appropriate approvals. Outcome monitoring is performed to inform decisions about continuing with the new IP/D or abandoning/pausing if safety data show signals of harm; this is the responsibility of local hospitals. Hospital policies for this process have hitherto not been investigated.Aim To explore local hospital NPC processes for monitoring clinical and safety outcomes and decision-making regarding the delivery of new IP/Ds.Methods NHS organisation policies for the introduction of new IP/Ds from England and Wales were systematically examined using a standardised extraction form developed a priori. All policies and associated documents were analysed using the principles of content analysis, and information extracted included (1) the collection of safety and outcome data for approved IP/Ds; (2) requirements to adhere to NICE guidance and (3) how committees decide to abandon/pause the use of new IP/Ds.Results All policies (n=113) included information about monitoring outcomes of new IP/Ds. Substantial variation between hospitals in monitoring requirements was observed. Just 66 provided details of safety reporting oversight methods. Only 72 policies explicitly recommended following NICE IPAC guidance for the IP. Information about how decisions were made to abandon/pause new IP/Ds was included in 25 policies.Conclusion There is a disparity among hospitals in how outcome and safety data of new IP/Ds are monitored. This has implications for patient safety. Our findings support the IMMDS report recommendations for the need for better oversight and governance of innovative IP/Ds, including collecting and sharing robust outcome data to inform decision-making.